Contemporary dilemmas in the integration of ethics, medicine and law: a need for legal solutions - Jahn Kassim, Puteri Nemie; Alias, Fadhlina (2019)
The disciplines of medicine, ethics and law have always shared a close and strong connection. This can be seen from the early ages, where the cohesion between these three disciplines were infused in the functions of the medical doctor who was portrayed not just as a healer but as a judge and the law maker. The fact that doctors were able to heal the wounded and prolong death made them infallible as they appeared to possess supernatural powers with the ability to communicate with demons and divinity. However, as society transformed to become more vociferous and egalitarian, the predominance of law as an instrument of social regulation has become considerably evident. Legislative enactments and judicial interventions are currently social norms in defining the boundaries of rights and wrongful conducts in the practice of medicine. Self-regulation within the medical profession is perceived as a thing of the past and respectable medical opinion is no longer treated with excessive deference. Furthermore, the discipline of ethics in which principles on respecting autonomy, justice and dignity permeate the field of medicine, is also facing ongoing ethical conflicts which require solutions in the form of legal interventions. Accordingly, it can be seen that the interface between medicine, ethics and law has expanded rapidly and presents a very intricate area. It is therefore imperative that various socio-legal measures are introduced to assist the medical profession in facing these contemporary challenges and consequently, provide a more harmonious interface between medicine, ethics and law.